1982
DOI: 10.1042/bj2020445
|View full text |Cite
|
Sign up to set email alerts
|

Control of adenine nucleotide metabolism in hepatic mitochondria from rats with ethanol-induced fatty liver

Abstract: Male rats developed fatty liver after being fed on an ethanol-containing diet for 31 days. Liver mitochondria from these animals catalysed ATP synthesis at a slower rate when compared with mitochondria from pair-fed control rats (control mitochondria), and demonstrated lowered respiratory control with succinate as substrate, owing to a decrease in the State-3 respiratory rate. Respiration in the presence of uncoupler was comparable in mitochondria from both groups of rats. Translocation of both ATP and ADP was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
2

Year Published

1984
1984
2007
2007

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 21 publications
0
21
2
Order By: Relevance
“…Isolation of Rat Liver Mitochondria-Coupled liver mitochondria were prepared by differential centrifugation of liver homogenates (34,35) using ice-cold mitochondria isolation medium containing 0.25 M sucrose, 1 mM EDTA, and 5 mM Tris-HCl, pH 7.5. Protease inhibitors were added to the isolation buffer to prevent protein degradation (10).…”
Section: Methodsmentioning
confidence: 99%
“…Isolation of Rat Liver Mitochondria-Coupled liver mitochondria were prepared by differential centrifugation of liver homogenates (34,35) using ice-cold mitochondria isolation medium containing 0.25 M sucrose, 1 mM EDTA, and 5 mM Tris-HCl, pH 7.5. Protease inhibitors were added to the isolation buffer to prevent protein degradation (10).…”
Section: Methodsmentioning
confidence: 99%
“…Human hemoglobin and liver mitochondria were prepared as previously described. 24,25 Cytochrome c oxidase and citrate synthase activities were determined spectrophotometrically. 26,27 Oxygen and NO concentrations were measured simultaneously using Clark-type electrodes (Instech, Plymouth Meeting, PA; Harvard Apparatus, Holliston, MA) in a 1.0-mL sealed Perspex chamber, magnetically stirred at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Conclusive evidence shows that chronic alcohol exposure depresses the activities of all the oxidative phosphorylation complexes by approximately 30%-50%, exce pt Complex Ⅱ [15,16] . Inhibition of mitochondrial protein synthesis due to alcohol-mediated damage to the mitochondrial DNA [13,17] and ribosomes [18,19] is proposed to contribute to decreased functioning of the oxidative phosphorylation system and depressed rates of ATP synthesis [20,21] . Recently, studies by Cunningham and colleagues have shown that both hepatic energy charge and NADH-linked respiration are decreased in mitochondria isolated from liver of non-human primates allowed to consume alcohol for 18 mo [22] ; thus recapitulating the findings observed in rodent studies.…”
Section: Holic Liver Disease: Bioenergetic Defects and Oxidant Producmentioning
confidence: 99%